Ocular manifestations of psoriasis - Natasha Ferreira Santos da Cruz (Arquivos Brasileiros de Oftalmologia)
ABSTRACT Purpose: We aimed to report the ocular manifestations observed in patients with psoriasis. Methods: Patients were included and referred to our ophthalmology clinic from dermatology clinics of Universidade do Estado do Pará between October 2013 and August 2014. Clinical interviews were conducted to identify relevant epidemiological data, clinical features, and treatment details, and data were recorded using the same protocol. Subsequent dermatological examinations were performed and disease severity was rated using the Psoriasis Area and Severity Index and the Dermatological Life Quality Index. Complete eye examination was conducted, including visual acuity, biomicroscopy, tonometry, fundoscopy, Schirmer I test, tear breakup time, rose bengal staining, ocular surface disease index, and glaucoma tests. Results: In total, we included 43 patients with psoriasis and 86 controls. Patients with psoriasis had statistically higher incidences of dry eye (16.28%), likely dry eye (32.56%), and blepharitis (16.28%). Furthermore, the rose bengal and ocular surface disease tests were more abnormal in patients with psoriasis (p<0.05). Conclusions: Patients with psoriasis should undergo regular eye exams, regardless of risk factors, to monitor for the progression of symptomatic or asymptomatic ocular manifestations.